2020
DOI: 10.1029/2019jd031527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Simulated Drop Size Distributions and Microphysical Processes Using Polarimetric Radar Observations for Landfalling Typhoon Matmo (2014)

Abstract: The Morrison (Morr), Thompson (Thom), Thompson aerosol‐aware (ThomA), and WRF double‐moment 6‐class (WDM6) microphysics schemes within the WRF model are used to simulate landfalling Typhoon Matmo (2014) and evaluated against polarimetric radar observations in terms of raindrop size distribution (RSD) and microphysical processes. Focus is placed on the inner rainband convection. Only ThomA is able to reproduce observed RSD characteristics having even smaller mean raindrop sizes and larger number concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…The precipitation types (convection or stratiform) are identified using a robust method based on Steiner et al. (1995), which classify the convective and stratiform areas from the sharpness and intensity variations of the radar reflectivity values at 2‐km AGL height (Wang et al., 2016; Wen et al., 2018, 2020). Radar reflectivity from LSRD shows that the horizontal structure of the Meiyu system seems like the leading‐line trailing‐stratiform (TS) convective system type during its mature stage (Parker & Johnson, 2000).…”
Section: Evaluation Of Simulated Results Near Groundmentioning
confidence: 99%
See 3 more Smart Citations
“…The precipitation types (convection or stratiform) are identified using a robust method based on Steiner et al. (1995), which classify the convective and stratiform areas from the sharpness and intensity variations of the radar reflectivity values at 2‐km AGL height (Wang et al., 2016; Wen et al., 2018, 2020). Radar reflectivity from LSRD shows that the horizontal structure of the Meiyu system seems like the leading‐line trailing‐stratiform (TS) convective system type during its mature stage (Parker & Johnson, 2000).…”
Section: Evaluation Of Simulated Results Near Groundmentioning
confidence: 99%
“…Previous studies show that simulated radar variables from different types of precipitation systems (e.g., tropical cyclone, tropical maritime convection, and midlatitude continental storm) have similar statistical characteristics if the same microphysics scheme is used. For example, the simulated DR Z E of some specific microphysics schemes are much higher than radar observations near ground for all types of convective systems (Brown et al, 2016;Putnam et al, 2016;Wang et al, 2020). The biased values of these simulated polarimetric radar variables indicate the possible discrepancy of DSD distributions between model simulations and reality.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a subsequent article [9], it was shown that in stratiform rain from both hurricane rain bands and in MCSs, the treatment of melting snow to rain needed to be modified to predict the smaller values of Z DR consistent with observations. A similar explicit simulation of Typhoon Matmo comparing four different bulk microphysical schemes but focused on the inner rain band convection were used by [10]. They found that DSDs were dominated by warm rain processes, but the distributions were characterized by smaller values of mass-weighted mean diameter and much larger normalized intercept parameter relative to non-typhoon maritime convective rain [11,12].…”
Section: Surface Disdrometers and Npol Radarmentioning
confidence: 99%